A Mindful Character Development: Mindfulness and Self-Efficacy Enhances Emotional Regulation of High School Students - Emilia Putri Wahyuni; Hendri Ardianto; Sandjaja Dharmatanna; Burmansah Burmansah; Wistina Seneru; Rini Kasrah; Tejo Ismoyo (International Journal of Science and Applied Science: Conference Series, 2024)
This study explores the influence of mindfulness and self-efficacy on the emotional regulation of high school students. Emotion regulation is the ability of individuals to manage and control their emotions effectively, which is very important in students' psychological development. Along with the increasing academic and social demands among high school students, mindfulness and self-efficacy are essential to help better regulate emotions. This study uses a quantitative survey method. The research population was 139 high school students, with a sample of 104 students using the Proportionate Stratified Random Sampling technique. Data were collected through questionnaires tested for validity and reliability and then analyzed using multiple regression techniques to test the influence of mindfulness and self-efficacy on emotional regulation. The study showed that mindfulness and self-efficacy positively and significantly affected students' emotional regulation. Mindfulness, which includes full attention to the physical body, feelings, and mind, has been proven to help students be more aware of their emotions and manage them more effectively. Self-efficacy, as an individual's belief in their ability to overcome challenges, is significant in helping students cope with difficult emotional situations.